Hubungan Kebiasaan Sarapan dengan Konsentrasi Belajar Anak Kelas 3-6 di SDN Plosomalang 02 Pati - Chanindya Anggita Putri; Nopi Nur Khasanah; Kurnia Wijayanti (Journal of Health, Medical, and Psychological Studies, 2026)
Students’ academic success is strongly influenced by their ability to maintain optimal learning concentration. A study conducted at SDN Plosomalang 02 Pati indicates that most students experience difficulties in maintaining focus, which are associated with irregular breakfast habits. This study aims to analyze the relationship between breakfast habits and learning concentration among students in grades 3–6 at SDN Plosomalang 02 Pati. The research employed a quantitative design with a cross-sectional approach. The sample consisted of the entire population of students in grades 3–6, totaling 68 participants, selected using a total sampling technique. The research instruments included a breakfast habits questionnaire and the Grid Concentration Test (GCT) to measure learning concentration. Data analysis was performed using the Spearman Rank correlation test to determine the relationship between variables. The results showed that the majority of students had breakfast habits in the “moderate” category (86.8%) and learning concentration levels in the “low” category (54.4%). Bivariate analysis demonstrated a positive and statistically significant relationship between breakfast habits and learning concentration (p-value = 0.007; R = 0.294). This indicates a significant relationship with weak correlation strength between breakfast habits and learning concentration. Therefore, schools and parents are encouraged to enhance their awareness and facilitate regular, nutritious breakfast consumption in order to optimize students’ concentration abilities and academic potential